Decentralized voltage control for efficient power exchange in interconnected DC clusters - Samende, C; Bhagavathy, S; Gao, F; McCulloch, M (Institute of Electrical and Electronics Engineers, 2020)
Interconnection of two autonomous DC clusters which are designed for energy access can increase power supply reliability for productive uses such as irrigation. Here, a surplus or a deficit power generation in one cluster is balanced by a second cluster through power exchange. Usually, the clusters are connected by a tie line if bus voltages in both clusters are equal and constant. If the bus voltages are different and constant, a single converter is used to interconnect the clusters and to control the power flow between them. In both interconnections, power flow is triggered by bus voltage variations from their constant values. However, if the bus voltages are different and are not constant, the coordination of the power exchange between the clusters is a challenge. In this paper, two bidirectional DC-DC converters are proposed to interconnect clusters that have different and unregulated bus voltages. To control the power exchange while reducing transmission line loss, a decentralized control method which is composed of a voltage droop control method and a mid-point voltage control method is proposed. Simulations of two interconnected clusters carried out in MATLAB/Simulink software show how the proposed control method can efficiently coordinate the power exchange.